Optimal Load Frequency Control for Interconnected Power Systems using Optimized PI-PD Controller with TCSC and HVDC Integration - Nath, Vivek; Sambariya, D.K (IAES Indonesian Section, 2023)
The aim of this study is to develop a consistent load frequency control system for a multi-area power system (PS) network that uses a variety of energy sources. The research focuses on improving frequency regulation and ensuring stability in the face of uncertainties and disturbances. This article introduces load frequency control (LFC) analysis for multi-area multi-source (MAMS) interconnected power systems (IPS). Each area comprises thermal reheat turbines, a hydro unit, and gas turbines as generating units. The effect of AVR after TCSC and HVDC is extensively investigated in this research article. The suggested hybrid PI-PD controller is tuned using the PSO optimization technique, presenting a novel and efficient approach to addressing the complexities of multi-area power systems. Another significant advancement is the incorporation of high-voltage direct current (HVDC) and thyristor-controlled series compensator (TCSC) as auxiliary parameters. This dual integration improves system robustness by managing power flow variations and enhancing transient response, ultimately contributing to the overall stability of the multi-area power grid. Four different power system models are studied. To determine the best value for controllers, all four performance metrics are employed to define the optimal parameters of the PI-PD and PID controller. Eigenvalues analysis is also conducted to find the stability of the MAMS power system. The robustness of the proposed PI-PD controller at different loading conditions is tested, and the superiority of the suggested controller is determined by executing it in four different cases. A step-load of 10% is applied for each area. Non-linearities such as governor dead band (GDB), governor rate constraints (GRC), and the boiler are also included in the MAMS-IPS. Based on settling-time (ST) and rise-time (RT), the performance of the proposed controller is compared with various PID controllers optimized with novel evolutionary algorithms from recent published literature. MATLAB 2018@ software is used for simulation purposes.